Carbon isotope discrimination in Quercus ilex resprouts after fire and tree-fell (Oecologia, 1996)
Ecophysiological differences related to photo- synthesis were compared in holm oak Quercus ilex leaves from undisturbed holm-oak vegetation, resprouts after fire and resprouts after tree-fell. No significant dif- ferences in any parameter measured were observed be- tween the two kinds of resprout throughout the first growing season following disturbance. Resprouting leaves showed lower carbon isotope discrimination (A) and intercellular CO 2 concentration (Pi), and higher pho- tosynthesis, leaf conductance and transpiration rates than leaves from undisturbed stands. Nitrogen, soluble protein content and ribulose bisphosphate carboxylase (RuBP- Case) activity were 88%, 96% and 45% higher respec- tively, in both kinds of resprout. The results indicate that photosynthetic capacity, rather than stomatal conduc- tance, is the limiting factor in photosynthesis in re- sprouts. Chlorophyll content and chlorophyll a/b ratio did not differ between resprouts and undisturbed leaves, indicating that the observed differences were not a result of differences in light environment during leaf develop- ment. Leaf mass per area (LMA), was 80% higher in the resprouts, and was negatively related (r= -0,86) to A and positively related (r=0.87) to N content. Enhanced car- bon assimilation after disturbances resulted in higher wa- ter use efficiency, as indicated by lower A values in the resprouts. We conclude that the cause of defoliation was not relevant in the physiology of the resprouts, suggest- ing the importance of underground organs.